La formation de l’élève-citoyen dans les instances lycéennes : quelles finalités ? quels apprentissages ? - Céline Chauvigné (Éducation et Socialisation)
Within the context of the development of citizenship education in schools, this article proposes to examine the functioning and way of understanding educating or training through upper secondary school and the delegation to see the tensions that animate it. The analysis of practionners’ work and activity itself and their testimonies we will allow us to reveal the elements of training or a deadlock in democratic school today.